A visual way to talk to strangers: authentication in wireless pervasive computing. (7th May 2010) - Shin, Dongwan; Claycomb, William; Im, Seunghyun
In this paper, we discuss a novel approach to identifying entities involved in ad-hoc wireless communications through using an effficient visual code system called UbiCode. UbiCode, used in an out-of-band channel in order to bootstrap trust between entities unknown to each other, facilitates a mechanism for demonstrative identification of entities involved, thereby enabling secure spontaneous communications among them in wireless pervasive computing environments. We present the design of the visual code system as well as different types of identification protocols leveraging the visual code system. We also demonstrate our approach through a proof-of-concept implementation.